Violence on Women and Children: Background, Effects, and Solutions - Rahmatika, Aulia Vaya (Faculty of Law Universitas Negeri Semarang, 2021)
Violence is any criminal conduct that may harm the victim. The violence occurred on a number of factors, including the factors economic, cultural, social, and legal. Today, violence is an awful lot going on in the community. See the rampant violence lately are influenced by the large number of people experiencing prolonged crisis due to oppression. The action also triggered by weak social control that is not followed by legal enforcement measures. There is also the violence done to women and children. Violence against women as a global problem, already fretting over every country in the world, not just the countries that are developing but also including developed countries which are said to be greatly appreciate and care about the human rights as United States of America. Indonesia as a country that is growing, it bore the title bad in the problem of human rights violations. Human rights violations are one of which violations of women's human rights. The women's human rights violations can be classed as acts of violence against women. Violence against women may occur anywhere (in a public place, in the workplace, the surroundings of family (household) and others. Can be done by anyone (parents, brothers or women and others and can occur at any time (day and night). In addition, the violence that occurs in children also resulted in mental decline. Children will feel depressed and prolonged trauma. It is certainly harmful for the child's mental and psychic condition. Violence in children usually occurs because a child who is misbehaving and not according towards parents so often parents furious and do acts of violence. This I will discuss to uncover cases of violence on women and children.